The economic benefits of whale watching in El Vizcaíno Biosphere Reserve, Mexico - Brenner, Ludger; Mayer, Marius; Stadler, Claudia (Economía Sociedad y Territorio, 2016)
This paper attempts to determine the economic value generated by whale watching at El Vizcaíno Biosphere Reserve/Lower California. Based on a representative sample survey, the analysis focuses on identifying specific visitor segments, their respective spending patterns, and the service sectors that profit. Results highlight that visitor spending generates a considerable gross turnover of just under $ 3,000,000 USD, benefitting mostly local tourism businesses. In order to increase the economic benefits of whale watching as a means of fostering sustainable regional economic development, it is crucial to focus tourism planning and marketing tools on well-defined visitor segments to satisfy their specific needs and expectations.